Parallel and distributed computation of a fingerprint access control system / Bopatriciat Boluma Mangata ... [et al.] - Mangata, Bopatriciat Boluma; Muamba, Kadima; Khalaba, Fundji; Parfum, Bukanga Christian; Mbambi, Kisiaka (Universiti Teknologi MARA, Perlis, 2022)
This work evaluates the runtime performance of a single-mode biometric recognition system for fingerprint-based access control to secure premises. To speed up the computation time in this system, we resorted to parallel programming, targeting more loops in the verification module. Our approach would therefore be to parallelize all loops that are computationally intensive during the verification of fingerprints in the database. On this, we exploited Microsoft's Task Parallel Library, specifically exploiting the for and for each loop. On the test set performed in sequential and parallel versions in the different data sizes, namely 50, 100, 150, 200, 250, 300, 350, 400, 450, 500, 550, and 600, we can state that the results obtained by the sequential and parallel implementations of our performance test programs allowed us to determine the best approach. Therefore, it is very clear that the sequential program is too greedy in terms of computation time compared to the parallel program which minimizes the computation time.